2016
DOI: 10.3390/ijerph13121241
|View full text |Cite
|
Sign up to set email alerts
|

Synergising Public Health Concepts with the Sendai Framework for Disaster Risk Reduction: A Conceptual Glossary

Abstract: The Sendai Framework for Disaster Risk Reduction (2015) is a global strategy for addressing disaster risk and resilience that has been ratified by member countries of the United Nations. Its guiding principles emphasise building resilience through inter-sectoral collaboration, as well as partnerships that facilitate community empowerment and address underlying risk factors. Both public health and the emergency management sector face similar challenges related to developing and implementing strategies that invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
(74 reference statements)
0
35
0
Order By: Relevance
“…Research and reports over the last 5 years not only have highlighted the need to empower people with disabilities (Phibbs et al 2016;Castro et al 2017;Quaill et al 2019), but also note that inclusivity has not been fully achieved by all Grant 2018;King et al 2019). People with disabilities, disability organizations, and care providers can and should contribute to disaster risk reduction and mitigation (Bennett et al 2017;Castro et al 2017;Gray 2017;Maini et al 2017;Grant 2018;Lunga et al 2019).…”
Section: Enhancing Disaster Preparednessmentioning
confidence: 99%
See 1 more Smart Citation
“…Research and reports over the last 5 years not only have highlighted the need to empower people with disabilities (Phibbs et al 2016;Castro et al 2017;Quaill et al 2019), but also note that inclusivity has not been fully achieved by all Grant 2018;King et al 2019). People with disabilities, disability organizations, and care providers can and should contribute to disaster risk reduction and mitigation (Bennett et al 2017;Castro et al 2017;Gray 2017;Maini et al 2017;Grant 2018;Lunga et al 2019).…”
Section: Enhancing Disaster Preparednessmentioning
confidence: 99%
“…Perhaps there are additional indicators to consider. Phibbs et al (2016) presented seven concepts that resonate with contemporary public health practice that would assist with enhancing disaster preparedness, which include the social determinants of health and inequality and inequity, among others. These studies identify the potential for a real increase in social and human capital for people with disabilities; furthermore, some studies showed that by providing a voice to the voiceless, attitudes shifted towards inclusiveness (Ronoh 2017).…”
Section: Enhancing Disaster Preparednessmentioning
confidence: 99%
“…This shift is also evident in the Sendai Framework for Disaster Risk Reduction 2015–2030 (Sendai Framework) adopted in March 2015 in Sendai, Japan by 187 UN members [7,8]. The goals and priority areas for action within the Sendai Framework have particularly stressed disaster risk reduction (DRR) [9]. According to the UNISDR, DRR refers to the concept and practice aim to analyze and reduce the causal factors of disasters induced by natural hazards, such as earthquake, floods, droughts, and cyclones; initiatives of DRR not only involve various disciplines including but not limited to disaster management, disaster mitigation, and disaster preparedness, but also links every part of society, government and every part of professional and private sectors [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Practices of were DRR thereby encouraged for building resilience to current and future disaster risks [9]. Resilience can be considered at different levels including individual, family, community, state or ecological system [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…The intersection of factors such as age, gender, disability, and income with social isolation has been found to increase vulnerability, and impede response, to natural disasters (Howard, Agllias, Bevis, & Blakemore, 2018). Therefore, it has been suggested that national campaigns involving public education to raise awareness of disaster risk, preparation and recovery should consider specific audiences and their needs to reduce inequity and become more effective to strengthen community resilience than focusing on individual behaviour as the target of intervention (Phibbs, Kenney, Severinsen, Mitchell, & Hughes, 2016). Despite some of these limitations, the strengths of the research include discovering key resilience characteristics of women and the methods used have arguably mitigated these limitations and offered insight into the important role women play post-disaster.…”
Section: Limitationsmentioning
confidence: 99%